2020
DOI: 10.22541/au.159015263.38072348
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Management of new onset anosmia during the COVID pandemic - BRS Consensus Guidelines

Abstract: Objectives The primary aim of the study is to provide recommendations for the investigation and management of patients with new onset anosmia during the COVID-19 pandemic Design After undertaking a literature review, we used the RAND/UCLA methodology with a multi-step process to reach consensus about treatment options, onward referral imaging. Setting and participants An expert panel consistent of 15 members was assembled. A literature review was undertaken prior to the study and evidence was summarised for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
0
5
0
2
Order By: Relevance
“…The Exerscent device might facilitate olfactory research in several ways. First, smell training conducted outside of the lab could be valuable as a therapeutic intervention to counter smell loss, for example, due to coronavirus infection (Gerkin et al, 2020;Hopkins et al, 2020). Here, the Exerscent digital interface will enable more sophisticated data collection and user feedback, and more flexible task designs.…”
Section: Discussionmentioning
confidence: 99%
“…The Exerscent device might facilitate olfactory research in several ways. First, smell training conducted outside of the lab could be valuable as a therapeutic intervention to counter smell loss, for example, due to coronavirus infection (Gerkin et al, 2020;Hopkins et al, 2020). Here, the Exerscent digital interface will enable more sophisticated data collection and user feedback, and more flexible task designs.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest four primary research application areas for the Exerscent device. First, smell training conducted outside of the lab could be valuable as a therapeutic intervention to counter smell loss due to COVID-19 symptoms and other anosmias (Gerkin et al, 2020;Hopkins et al, 2020). Here, the Exerscent digital interface will enable more sophisticated data collection and user feedback, and more flexible task designs.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown sensory benefits of smell training after postviral olfactory loss (Hummel et al, 2009;Sorokowska et al, 2017). Smell training has been recommended as a means to recover olfaction following COVID-19 (Hopkins et al, 2020). Smell training has also shown to enhance olfactory perception and cognition, and arguably even non-olfactory cognitive abilities, suggesting a wide range of applications (Birte-Antina et al, 2018;Olofsson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 virusas ne išimtis. Pastarasis infekuoja ląsteles pasinaudodamas angiotenziną I konvertuojančio fermento 2 (AKF2) receptoriais ir ląstelių paviršiaus proteazėmis TMPRSS2 [8]. Kelios studijos teigia, jog nosies kvėpuojamojo epitelio ląstelės pasižymi didesne AKF2 receptorių ir TMPRSS2 genų raiška, nei trachėjoje ar plaučiuose [9], todėl būtent nosies epitelis yra pagrindinis viruso rezervuaras užsikrėtus koronavirusu.…”
Section: Tyrimo Rezultatai Ir Diskusijaunclassified
“…Šios ląstelės tiesiogiai atsakingos už hematoencefalinį barjerą, vietinio kraujagyslių tonuso palaikymą ir neuroimuninį atsaką [12]. Tai leidžia manyti, jog virusas, patekęs į pericitus, gali tiesiogiai (dėl perfuzijos pokyčių) arba netiesiogiai (dėl uždegimo) paveikti chemosensorinį suvokimą smegenyse [8]. Bandant išsiaiškinti, ar CO-VID-19 virusas gali tiesiogiai paveikti CNS neuronus, kyla daug diskusijų, tačiau iš esmės virusas turi galimybę patekti į smegenis net keliais skirtingais būdais per kraujagysles, nervus, kurie inervuoja infekuotus audinius, ir tiesiogiai per nosį (akytąją plokštelę).…”
Section: Vaizdo Tyrimaiunclassified